A reanalysis of the Chilean ocean circulation: preliminary results for the region between 20°S to 40°S - Aiken,Christopher M (Pontificia Universidad Católica de Valparaíso. Facultad de Recursos Naturales. Escuela de Ciencias del Mar, 2017)
The development and initial results from a reanalysis, or best estimate, of the historical state of central Chile's coastal ocean are presented. The Chilean Ocean State Estimate (COSE) covers the western coast of South America southwards of 20°S and for the period 1993 to 2012. The reanalysis is being performed using the 4DVAR driver of the Regional Ocean Modeling System (ROMS). The ROMS solution is constrained to reconcile satellite sea surface temperature and altimetry data with prior estimates of the initial state and boundary conditions derived from the HYCOM (Hybrid Coordinate Ocean Model) global reanalysis. Here we present preliminary results from COSE for central Chile and the year 2008. The regional reanalysis reduces the model-observations mismatch of the global HYCOM solution by 38 and 27%, for sea surface temperature and height respectively, and corrects a spurious on-shore surface current present in the HYCOM reanalysis. Inspection of the assimilation increments suggests that ROMS simulations forced by satellite winds overestimate coastal upwelling.